The Effects of E-Tourism to The Development of Tourism Sector in Indonesia - Jonathan, Claresta Janice; Tarigan, Riswan (CommIT (Communication and Information Technology) Journal, 2016)
Indonesia is a nation that ethnically and culturally unique and diverse. It has potentials to leverage the growth of its tourism sector. The sector has become important to boost not only regional and also  nation- wide economic development. It can be growth further to a much larger scale by effectively utilising the pervasiveness of the information and communication technology (ICT). For example, ICT may facilitate the growth with e- tourism, which is an Internet-based marketing method. This work intends to understand the potential of using e-tourism and its effects on the development of  the  sector. Specifically, the study evaluates how the aspects  of marketing, business, and e-tourism are affected by the use of ICT and how they affect the growth of the tourism industry. A multivariate regression model is constructed to assess the case quantitatively. The empirical model suggests that the e-tourism may contribute the growth of the tourism sector by about 40%.